Respostas pressóricas do pilates e a influência da respiração desse método na pressão arterial de mulheres hipertensas - Santos, Aline da Silva Adães Motta dos (2016)
Aerobic exercise is well established in the literature as one of the non-pharmacological interventions in the treatment of hypertension. There is some controversy about resistance training and there is a paucity of evidence about sports such as Pilates. Because it is a widespread and practiced activity, it is necessary to know their hemodynamic responses and if there is possibility of post-exercise hypotension. Objective: To analyze the acute hemodynamic responses and to verify the occurrence of hypotension and mitigation of pressure reactivity after a Pilates session, and analyze if breathing is an active component in these responses. Method: 30 women (63.7 ± 5.8 years) were randomized into three groups (n = 10), which underwent a Pilates session with the respiratory component, the respiratory component and not only the breathing exercises each. The following variables were analyzed in the pre- and post-exercise period: Systolic and Diastolic Blood Pressure, FC and Reactivity pressure, and BMI, waist circumference, hip and abdomen. Results: The results show that one Pilates session is not able to significantly reduce BP in hypertensive subjects, nor ease the pressure reactivity. Besides, specific breathing technique of the method appears not to be an active component in reducing blood pressure. Although there was no statistical significance of these results, we believe that the amplitudes of found mitigations are relevant, since resemble those caused reductions by an anti-hypertensive medication class or for nutritional education and these minimum reductions in SBP are associated with decreased the risk of mortality from cardiovascular disease.